2017
DOI: 10.1016/j.jalz.2017.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Association of amine biomarkers with incident dementia and Alzheimer's disease in the Framingham Study

Abstract: INTRODUCTION The identification of novel biomarkers associated with Alzheimer’s disease (AD) could provide key biological insights and permit targeted preclinical prevention. We investigated circulating metabolites associated with incident dementia and AD using metabolomics. METHODS Plasma levels of 217 metabolites were assessed in 2067 dementia-free Framingham Offspring Cohort participants (mean age=55.9±9.7 years; 52.4% women). We studied their associations with future dementia and AD risk in multivariate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
72
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 106 publications
(79 citation statements)
references
References 59 publications
4
72
2
Order By: Relevance
“…In this exploratory metabolomics study, untargeted (global) metabolomics analyses were performed to characterize plasma profiles of women with FM compared with women without FM with the goal of identifying differential metabolites as potential biomarkers involved with FM pathogenesis. Because of the small sample size and the cross‐sectional design of our study, we did not conduct pathway analysis but report on select metabolites that suggest a potential for clinically meaningful health consequences in persons diagnosed with FM . Study findings are intended to inform the direction for conducting future targeted metabolomic research.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In this exploratory metabolomics study, untargeted (global) metabolomics analyses were performed to characterize plasma profiles of women with FM compared with women without FM with the goal of identifying differential metabolites as potential biomarkers involved with FM pathogenesis. Because of the small sample size and the cross‐sectional design of our study, we did not conduct pathway analysis but report on select metabolites that suggest a potential for clinically meaningful health consequences in persons diagnosed with FM . Study findings are intended to inform the direction for conducting future targeted metabolomic research.…”
Section: Discussionmentioning
confidence: 99%
“…The KP is understood as the primary route in the metabolism of tryptophan (Trp), an essential amino acid known to be a precursor to both serotonin and melatonin. Altered metabolism along the KP has been associated with psychiatric disorders such as depression and neurological disorders such as mild cognitive impairment and dementia . For example, in a sample of 2,067 dementia‐free Framingham Offspring Cohort participants, Chouraki et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, whether it is effective or not is still unknown. KP plays an important part in neurodegenerative disorders including Alzheimer's disease (Chouraki et al, 2017;Giil et al, 2017). Studies have shown that AD patients suffered with increased tryptophan through significantly decreased KYNA (Hartai et al, 2007) and increased level of QUIN (Gulaj, Pawlak, Bien, & Pawlak, 2010).…”
Section: Alzheimer's Diseasementioning
confidence: 99%